Immigration and Housing Rents: Short-Run Effects of the 2015 Refugee Crisis in Germany - Kathleen Kürschner Rauck; Michael Kvasnicka (Journal of Regional Science, 2025)
We study the impact of the 2015 mass arrival of refugees in Germany on housing rents. Using data on county-level refugee populations and offers of flats for rent from Germany's leading online property broker ImmobilienScout24 , we find strong and robust evidence in DiD and IV regressions that refugee immigration adversely affected rental price growth. Additional explorations into native (German) mobility responses, related housing market metrics, and regional effect heterogeneity by prevalence of anti-refugee crimes, crimes against natives involving refugee suspects, neighborhood (1 km grid) characteristics, and local exposure to different types of refugee housing suggest that perceptions of refugee immigration as a (source of) disamenity are major drivers of our findings.
Keywords: 320; Germany; housing rents; refugee migration